2012
DOI: 10.1371/journal.pone.0039049
|View full text |Cite
|
Sign up to set email alerts
|

Regional Susceptibility to TNF-α Induction of Murine Brain Inflammation via Classical IKK/NF-κB Signalling

Abstract: It is becoming clear that inflammation plays a significant role in a number of neurological and psychiatric conditions. Post mortem brain samples in Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, multiple sclerosis, schizophrenia and most recently autism spectrum condition, all exhibit neuroglial activation and inflammatory markers within the CSF. Many questions remain about the underlying molecular mechanisms. By adding the pro-inflammatory cytokine, TNF-α, to mouse brain tissue we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 33 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…However, when NF-kB transcription is activated by excessive amounts of TNF-a, it leads to production of excitotoxins, reactive oxygen species, and additional proinflammatory cytokines, which, in turn, leads to apoptosis in the absence of active feedback systems. 33,34 Whether and how any of these pathways are involved in ASD will need to be addressed by future experimental studies in mouse models of ASD and confirmed by correlative clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, when NF-kB transcription is activated by excessive amounts of TNF-a, it leads to production of excitotoxins, reactive oxygen species, and additional proinflammatory cytokines, which, in turn, leads to apoptosis in the absence of active feedback systems. 33,34 Whether and how any of these pathways are involved in ASD will need to be addressed by future experimental studies in mouse models of ASD and confirmed by correlative clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Canonical NF-κB activation triggers the production of cytokines such as IL1β, IL6(51) and IL12, and is inhibited by RPS6KB1 (S6K1). Knockdown of this inhibition results in enhanced production of inflammatory cytokines(19).…”
Section: Discussionmentioning
confidence: 99%
“…TNF- α was specifically selected to activate the classical NF- κ B signaling cascade of the innate immune system and to stimulate the nuclear translocation of NF- κ B in primary cortical neurons [ 58 ]. NF- κ B DNA binding activity was significantly increased in the peripheral blood samples of children with autism [ 59 ].…”
Section: Cytokines and Autismmentioning
confidence: 99%